Prime Minister’s Decree No. 1539 of the year 2025 Amending Certain Provisions of the Executive Regulations of the Capital Market Law Promulgated by the Minister of Economy and Foreign Trade Decree No. 135 of 1993 = قرار رئيس مجلس الوزراء رقم 1539 لسنة 2025 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق رأس المال الصادرة بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.